Perancangan Masjid Joko Agung Purnomo: Arsitektur Islam Kontemporer di Lembang, Kabupaten Bandung Barat - Nafi' Athoya Al Hikmah; Mohammad In Am Ainul Yaqin (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
The construction of worship facilities in densely populated urban areas in Indonesia often faces constraints regarding limited land and the inability to renovate existing structures. This study examines the architectural design of the Joko Agung Purnomo Mosque, a two-story mosque currently under construction in Lembang, West Java, built on a new site provided by a donor as a solution to the overcapacity of surrounding existing mosques. Using a qualitative descriptive method with an architectural design analysis approach, this research focuses on how the design integrates contemporary Islamic architectural principles with tropical climate responsiveness. The findings indicate that limited land is addressed through the application of a vertical space system to optimize the worship area. In response to the tropical climate, the design utilizes a central void, serving as the primary strategy for natural lighting and cross-ventilation. Structurally, the building utilizes reinforced concrete (columns, beams, and ring beams) with a light steel roof truss and spandex roofing. Islamic identity and ecological function are realized through the application of mashrabiyya geometric patterns on the arched facade openings, which successfully combine visual identity with passive ventilation systems.